PERAN ACCOUNT EXECUTIVE DAN FINANCE MANAGER DALAM KAMPANYE KOMUNIKASI PEMASARAN DEBIURYN COSMETICS SEBAGAI PENGUATAN BRAND POSITIONING PADA KALANGAN REMAJA USIA 12–19 TAHUN DI KOTA SEMARANG - Agatha Samuella; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This project analyzes the “Stay Bright, Stay Youth” marketing communication campaign implemented by DeBiuryn Cosmetics, a skincare brand targeting teenagers. The campaign was designed to reinforce brand positioning, enhance brand awareness, and stimulate sales among adolescents aged 12–19 in Semarang City. An integrated communication approach was applied by combining digital marketing activities on Instagram and TikTok with offline initiatives, including the DeBiuryn Class Out event and Glow On the Booth DeBiuryn. In this project, the author assumed the roles of Account Executive and Finance Manager, acting as a liaison between the internal team, clients, and external stakeholders, preparing meeting documentation, and managing financial responsibilities. These responsibilities included budgeting, financial reporting, discount calculations, sales target planning, and the compilation of product sales data. The evaluation results reveal a substantial improvement in brand awareness, increasing from 14% to 84.8%. Moreover, the campaign exceeded the sales targets for the Youth Series products, with Youth The Better Cleanser recording sales of 112 units against a target of 90 units, while Youth Go Away Sun SPF 30+++ reached 92 units from a target of 90 units. These results indicate that a well-executed integrated marketing communication strategy can effectively strengthen brand pMositioning and drive sales growth. Furthermore, this campaign demonstrates potential for long-term development as a sustainable program to foster consumer loyalty and strengthen brand equity within the teenage skincare market.